UPAYA PENINGKATAN HASIL BELAJAR SISWA DI JAM TERAKHIR DENGAN MENGGUNAKAN MEDIA INTERAKTIF QUIZZIZ PAPER MODE DI KELAS IV SD INPRES LAMBENGI - Linda Pajarwati; Ulfa Dwianti; Andi Kartini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Integration of technology in learning is important to create a more interesting and effective learning experience. Many digital learning applications can be used effectively and supporting media for learning. This study requires innovation in learning media so that students do not feel bored during the teaching and learning process. The purpose of this study is to determine the increase in student learning outcomes in the material on plant body parts of class IV B at SDI Lambengi with 30 students as research subjects. This type of research is Classroom Action Research (CAR). Data collection using test, observation and documentation methods. The results of this study are; there is an increase in average learning outcomes and percentages in cycle I of 73.3% and cycle II of 90%.